(untitled) (Razão e Fé, 2023)
The objective is to present some predictions about the conception of pedagogy outlined in the thought of the German philosopher Immanuel Kant (1724- 1804), focusing exclusively on the introductory part of the work On Education. For Kant, the main purpose of education is to develop human nature with a view to the progress of humanity. The human being is born as one of the most resistant animals, so he needs to be careful and be under the guardianship of another at the beginning of his life. But it also has the potential for morality, which needs to be stimulated in order to emerge. In this sense, education presents itself as a condition of possibility for the humanization of the human being. As human nature, by itself, does not have sufficient conditions to carry out such a task, education appears as an ideal project capable of leading humanity to a stage of perfectibility.